23rd Annual Congress of the European College of Sport Science (ECSS), 4th-7th July, Dublin, Ireland. Book of Abstracts (23rd Annual Congress of the European College of Sport Science (ECSS), 4th-7th July, Dublin, Ireland. Book of Abstracts, 2018)
TABLE OF CONTENT